2016
DOI: 10.1177/0038038515596896
|View full text |Cite
|
Sign up to set email alerts
|

Are Immigrants Really Lacking Social Networking Skills? The Crucial Role of Reciprocity in Building Ethnically Diverse Networks

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…For example, sociology and anthropology research examines how social relationships and networks can pressure multicultural individuals towards or away from their own cultural groups (e.g., James, Jenks & Prout, 1998;Ngo, 2008;Windzio, 2015), especially for those with lower power or status, or whose ethnic ancestry is visibly different from the mainstream in a society (e.g., Gowricharn & Çankaya, 2017;Siebers, 2015). A combination of socio-political factors, including societal attitudes about minorities, country-level policies related to immigrants, and level of cultural diversity in an area, have been shown to influence individual-level multiculturalism (e.g., Barwick, 2017;Bean, Brown, Bachmeier, Fokkema, & Lessard-Phillips, 2012;Berry, 1997;Korac, 2003).…”
Section: Conceptualizing Multiculturalismmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sociology and anthropology research examines how social relationships and networks can pressure multicultural individuals towards or away from their own cultural groups (e.g., James, Jenks & Prout, 1998;Ngo, 2008;Windzio, 2015), especially for those with lower power or status, or whose ethnic ancestry is visibly different from the mainstream in a society (e.g., Gowricharn & Çankaya, 2017;Siebers, 2015). A combination of socio-political factors, including societal attitudes about minorities, country-level policies related to immigrants, and level of cultural diversity in an area, have been shown to influence individual-level multiculturalism (e.g., Barwick, 2017;Bean, Brown, Bachmeier, Fokkema, & Lessard-Phillips, 2012;Berry, 1997;Korac, 2003).…”
Section: Conceptualizing Multiculturalismmentioning
confidence: 99%
“…They are fundamentally concerned with the structure of links or ties between nodes (e.g. between groups or individuals; Barwick, 2017). Anthropology and sociology research suggests that ties to people of different cultures can influence individual-level multiculturalism.…”
Section: Organizational Social Network and Individual-level Multiculmentioning
confidence: 99%
“…The social closure based on ethnic background is more common among Estonians (cf. Barwick ), and they only tend to establish relationships of trust, mutuality and reciprocity (cf. Ryan ) with minorities who are more like themselves.…”
Section: Results: Decreased Segmentation But Persistent Segregation Dmentioning
confidence: 99%
“…Regions can also play a vital role, as the differences in economic performance between, for example, north-west and south-east Europe, or east and west Germany illustrate. Moreover, as my own research has shown, the neighbourhood level can function as another significant marker: second-generation Turkish Germans experience much more discrimination in middle-class, native-German-dominated neighbourhoods than in ethnically and socioeconomically mixed ones (Barwick 2017).…”
Section: The National and Local Contexts As Push And Pull Factors Formentioning
confidence: 92%